2015
DOI: 10.1186/s12889-015-2409-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypoadiponectemia with smokeless/dipping tobacco use in young men

Abstract: BackgroundLow levels of adiponectin, an adipocytokine with anti-diabetic, antiatherogenic and cardioprotective properties, is associated with increased risk of coronary disease in young men. Previous studies have demonstrated that smokeless tobacco is linked with a reduction of plasma adiponectin levels. However, the influence of smokeless tobacco (dipping tobacco) on plasma adiponectin levels still remains unknown. This study was conducted to assess the plasma adiponectin levels in young men who were using di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…One review suggested that current smokers have reduced ADPN levels and that this reduction can be reversed by quitting smoking [12]. Another study suggested that tobacco use was significantly associated with a low ADPN level in communitydwelling young males [43]. The present study showed a significant interaction between ADPN rs266729 and ND.…”
Section: Discussionsupporting
confidence: 49%
“…One review suggested that current smokers have reduced ADPN levels and that this reduction can be reversed by quitting smoking [12]. Another study suggested that tobacco use was significantly associated with a low ADPN level in communitydwelling young males [43]. The present study showed a significant interaction between ADPN rs266729 and ND.…”
Section: Discussionsupporting
confidence: 49%
“…Thus, smoking could be an imperative element to evaluate testosterone level. Moreover, our group recently demonstrated a decreased level of adiponectin (hypoadiponectemia) in young men using smokeless tobacco (Ahmad et al, ).…”
Section: Introductionmentioning
confidence: 94%